2000
DOI: 10.1086/315516
|View full text |Cite
|
Sign up to set email alerts
|

Increased Level of Interferon‐α in Blood of Patients with Insulin‐Dependent Diabetes Mellitus: Relationship with Coxsackievirus B Infection

Abstract: The activation of the interferon (IFN)-alpha system and its relationship with coxsackievirus B (CVB) infection has been analyzed in 56 patients with insulin-dependent diabetes mellitus (IDDM; 25 children and 31 adults). Elevated levels of IFN-alpha were found in plasma of 70% of patients (39/56), and a positive detection of IFN-alpha mRNA in blood cells by reverse transcriptase-polymerase chain reaction (RT-PCR) was observed in 75% of patients (42/56). Enterovirus (EV) RNA assayed by seminested RT-PCR was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 161 publications
(132 citation statements)
references
References 52 publications
7
122
0
3
Order By: Relevance
“…Our interest in the blood comes from the fact that enteroviral RNA of CVB subgroup members, especially CVB4, was detected in human blood from patients with type 1 diabetes with nucleotide sequence homologous to CVB4 E2 in some patients (6,20). In an experimental model based on inbred male SWR mice inoculated with CVB3 by the intraperitoneal route (16), viral RNA was detected by quantitative RT-PCR in blood up to day 14 p.i.…”
Section: Cd8mentioning
confidence: 99%
“…Our interest in the blood comes from the fact that enteroviral RNA of CVB subgroup members, especially CVB4, was detected in human blood from patients with type 1 diabetes with nucleotide sequence homologous to CVB4 E2 in some patients (6,20). In an experimental model based on inbred male SWR mice inoculated with CVB3 by the intraperitoneal route (16), viral RNA was detected by quantitative RT-PCR in blood up to day 14 p.i.…”
Section: Cd8mentioning
confidence: 99%
“…Seroepidemiological data implicated largely enteroviruses, especially type B coxsackieviruses (CV-B), in type 1 diabetes development [Helfand et al, 1995;Hyöty et al, 1995] and several studies observed the presence of nucleotide sequences of those viruses in the blood of patients with that disease (reviewed by Hyöty et al, 2002). Among CV-B or enterovirus genus, CV-B4 is one of the serotypes most frequently associated with the disease in prediabetic and diabetic patients [Gamble et al, 1973;Chehadeh et al, 2000b]. The diabetogenic strain CV-B4 E2 was isolated from the pancreas of a child who died from diabetic ketoacidosis and was able to induce hyperglycaemia in some susceptible mouse strains [Yoon et al, 1979].…”
Section: Introductionmentioning
confidence: 99%
“…The process, which finally leads to complete beta-cell loss and onset of clinical disease, starts years before any clinical symptoms and is thought to result from several factors involving host genes, autoimmune responses and cytokines, as well as environmental factors. Results from previous cross-sectional and prospective studies on patients with Type 1 diabetes and/or prediabetic individuals have suggested that enterovirus infections are involved in the development of the disease [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15].…”
mentioning
confidence: 99%